(untitled) (Journal of Asian Development Studies, 2024)
This paper explores the subalternity of Indian widows due to patriarchy in Sidhwa’s novelWater.The study is conducted from the Spivakian perspective of subalternity enunciated in her canonical essayCan the Subaltern Speak?The study is qualitative-interpretive. In Indian society, widows are considered subalterns and inauspicious once their husbands are dead. They have no active role to play in the society. The male dominance in society hinders the social mobility of widows. The analysis and interpretation of the selected novel’s relevant text show that the males’ privilege to remarry is denied to females, fully endorsed by the Brahman religious dispensation. All the powers of decision-making lie with males.Similarly, the male members neither own the widowed women nor provide them with their due share in the familial property. As a result, they end up in ashrams and are excluded from mainstream society. This paper concludes that widows are rendered victimized, marginalized, and voiceless due to discrimination caused by patriarchy. They cannot speak for themselves, as per Spivakian’s perspective. The oppression of the Third World widows through patriarchy needs to be highlighted, and there is a dire need for sensitizing the conscience of the public to alleviate the plight of the widows through theuse of literature so that the voice of widows reaches the wider world.